Human capital development : resilience and sustainability - Santosh Vishnu Bhave (Kolkata National Institute of personnel management, 2024)
NATION 2024. 40th NIPM National conference; Research compendium PERSONNEL TODAY Vol.10-Sept 2024
Keywords: Management; statistical analysis; human capital